2018
DOI: 10.1159/000486715
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Otolaryngologic Manifestations in Children with Pseudohypoparathyroidism

Abstract: Background/Aims: Pseudohypoparathyroidism (PHP) is a rare, genetic disorder. Patients with PHP may have increased prevalence of obstructive sleep apnea (OSA) but this has not been prospectively studied. Methods: We enrolled children aged 6–18 years with PHP and matched controls. Evaluation included physical examination, medical history, and polysomnography. Results: Fifteen children with PHP type 1A (PHP1A) and 15 controls completed the study. Both groups were obese (BMI 32.2 ± 8.7 vs. 31.7± 6.5). The majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Sleep apnea, a well-known complication of obesity, has been reported to be more frequent in patients affected with PHP1A [77, 78] and may also be present in acrodysostosis [40]. Phenotypically, these patients present with round faces, a flattened nasal bridge, and/or maxillary hypoplasia [26, 50] which, combined with obesity, mechanically contributes to the development of sleep and respiratory disturbances [70, 77].…”
Section: Obesitymentioning
confidence: 99%
“…Sleep apnea, a well-known complication of obesity, has been reported to be more frequent in patients affected with PHP1A [77, 78] and may also be present in acrodysostosis [40]. Phenotypically, these patients present with round faces, a flattened nasal bridge, and/or maxillary hypoplasia [26, 50] which, combined with obesity, mechanically contributes to the development of sleep and respiratory disturbances [70, 77].…”
Section: Obesitymentioning
confidence: 99%
“…The prevalence of sleep apnoea in PHP1A (including both OSA and central apnoea) was found to occur at a 4.4-fold greater relative risk than similarly obese children in a retrospective study, which was out of proportion to the obesity alone [55]. A recent prospective study revealed that significant OSA occurred in 60% of children with PHP1A and seemed amplified possibly due to their craniofacial issues, along with an increased prevalence of hypotonia and asthma [22,56 ▪ ].…”
Section: Differences Between Pseudohypoparathyroidism Type 1a and Psementioning
confidence: 99%
“…However, during adolescence and early adulthood, energy expenditure is enhanced, whereas hyperphagia declines and, consequently, obesity is less pronounced in adulthood than in childhood ( 55 ). Although sleep apnea is a well-known complication of obesity, the observation that sleep disturbances are more often encountered (4.4-fold higher risk) in patients with PHP1A than in control subjects with comparable BMI is particularly intriguing ( 56 , 57 ). This highly unusual feature exactly tallies with Sleepy’s behavior.…”
Section: The Verdictmentioning
confidence: 99%